PEMBUATAN DAN UJI DAYA HAMBAT SEDIAAN SERUM WAJAH EKSTRAK DAUN PEPAYA (Carica papaya L.) TERHADAP staphylococcus epidermidis - Ramadani, Ananda; Rr. Widya Nurul Khatima; Erare, Friskila Bernadeta (Akademi Farmasi Yamasi Makassar, 2025)
This study aims to determine the inhibitory power of facial serum preparations from papaya leaf extract (Carica papaya L.) on the growth of Staphylococcus epidermidis. The research method carried out was experimental laboratory research, to determine the inhibitory power of facial serum from papaya leaf extract (Carica papaya L.) on the growth of Staphylococcus epidermidis which was carried out at the Microbiology Laboratory of the Yamasi Pharmacy Academy, Makassar. Papaya leaves were extracted using the maceration method using 96% ethanol solvent, the extract obtained was then made into a facial serum preparation with a concentration of 6% (F1), 8% (F2), 10% (F3) and as a serum base (F4). The research results stated that facial serum preparations of papaya leaf extract (Carica papaya L.) could inhibit the growth of Staphylococcus epidermidis with concentrations of 6%, 8%, and 10%.